Gingival Recession in Primary Maxillary Incisors due to Fingernail Scratching: A Rare Case Report - Dalal Maalem; Jalila Hammouti; Hind Ramdi (Case Reports in Dentistry)
Conclusion: This case highlights the importance of taking a comprehensive history and adopting a multidisciplinary approach to diagnose and manage self-inflicted gingival injury, achieving positive outcomes.